Pharmacist-led academic detailing intervention in primary care: a mixed methods feasibility study. - Riordan, David O; Hurley, Eimir; Sinnott, Carol; Galvin, Rose; Dalton, Kieran; Kearney, Patricia M; Halpin, James D; Byrne, Stephen (Springer Nature, 2019)
Background Academic detailing is a form of continuing medical education in which a trained health professional such as a physician or pharmacist visits prescribers in their practice to provide evidence-based information. While academic detailing has been adopted in other countries, this strategy is not routinely used in Ireland. Objective The aim of this study was to assess the feasibility and acceptability to General Practitioners (GPs) of a pharmacist-led academic detailing intervention in Ireland. Setting General Practice in County Cork, Ireland. Method A mixed methods feasibility study comprising a pharmacist-led academic detailing intervention on urinary incontinence in older people, quantitative data from patient medical records, and qualitative data from focus groups with GPs. The medical records for all patients aged ≥ 65 years who were attending a participating GP with a diagnosis of urinary incontinence were analysed using a before-after approach. The measures of prescribing assessed before and after the intervention were: LUTS-FORTA criteria, Drug Burden Index, and the Anticholinergic Cognitive Burden scale. Focus groups were carried out with GPs who participated in the academic detailing intervention. Main outcome measure The quantitative prescribing patterns of the GPs and their qualitative responses from the focus groups. Results Twenty-three GPs participated in the academic detailing intervention from a selection of different types of general practice. The medical records of 154 patients were analysed. There was minimal or no change in any of the prescribing measures used. Fourteen GPs attended focus groups. GPs considered the topic of urinary incontinence as relevant to general practice. Participants appreciated the succinct nature of the information in the educational materials but expressed a preference for a more easily retrievable format, such as an online version rather than paper-based. Conclusion This study demonstrated that a pharmacist-led academic detailing intervention was acceptable to GPs in Ireland. Further research is needed in a larger population evaluating the impact and cost effectiveness of academic detailing to optimise patient care.
Keywords: Drug prescriptions; Evidence-based education; Interprofessional relations; Ireland; Practice patterns; Primary care; Quality improvement; Aged; Aged, 80 and over; Attitude of Health Personnel; Education, Medical, Continuing; Electronic Health Records; Feasibility Studies; Female; Focus Groups; General Practitioners; Humans; Ireland; Male; Pharmacists; Practice Patterns, Physicians'; Primary Health Care; Professional Role; Qualitative Research; Urinary Incontinence